Green Synthesis and Antibacterial Activity of HAp@Ag Nanocomposite Using Centella asiatica (L.) Urban Extract and Eggshell - Xuan Nui Pham; Hoa Thi Nguyen; Ngan Thi Pham (International Journal of Biomaterials)
In recent years, the green synthesis of nanoparticles via biological processes has attracted considerable attention. Herein, we introduce a facile and green approach for the synthesis of poriferous silver nanoparticles (Ag-NPs) decorated hydroxylapatite (HAp@Ag) nanoparticles with excellent antibacterial properties. All the nanocomposites were fully characterized in the solid state via various techniques such as X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and energy-dispersive X-ray spectrometer (EDX), in which the synthesized Ag-NPs (24 nm in diameter) and their homogeneous incorporation on HAp have been studied by ultraviolet-visible (UV-vis) technique, transmission electron microscopy (TEM), and dynamic light scattering (DLS) analysis. The obtained results indicate that the structure and morphology of HAp have no significant changes after the incorporation of Ag-NPs on its surface. Moreover, an impressive antibacterial activity of HAp@Ag nanocomposite against Gram-positive bacterium Staphylococcus aureus and Gram-negative bacteria Escherichia coli and Pseudomonas aeruginosa has been recorded by using the agar well diffusion method. As a result, the HAp@Ag nanocomposite promises to be a great biomedical material with high antibacterial properties.